Analysis of equipment procurement delays at EVN Hanoi - Phuong, Thi Bich Thao; Do, Ba Khang; Vatcharapol Sukhotu; Claes, Marie-Therese; Electricity of Vietnam (EVN) (Pathumthani : Asian Institute of Technology, 2012)
Together with development of the country, Ha Noi Power Corporation has played successfully the key role in supplying power to Hanoi Capital at the annual growth rate of 10%-12%, fulfilling its contribution to state budget and actively participating into the social activities. During the coming years, besides the effective deployment of the traditional business areas such as business of electricity and telecommunication, EVN Hanoi will promote and expand the cooperation in business diversification-oriented investment and development, especially for the projects of power generation sources, finance and real estate. This is the business strategy suitable to the trend of economic growth of the capital and the country in the integration stage. With the higher demand to use electricity equipment, EVN Hanoi know that bidding process is the important process to have good successful bidder, supply high quantity equipment.
A project submitted in partial fulfillment of the requirements for the degree of Master of Business Administration (Executive) in International Business and Management of Technology, School of Management
Keywords: Electricity -- Equipment and supplies; Equipment and supplies